Different evolutionary patterns of hypoxia‐inducible factor α (HIF‐α) isoforms in the basal branches of Actinopterygii and Sarcopterygii. Issue 1 (19th September 2013) - Chi, Wei; Gan, Xiaoni; Xiao, Wuhan; Wang, Wen; He, Shunping
Abstract : Hypoxia‐inducible factor (HIF) is a crucial regulator of cellular and systemic responses to low oxygen levels. Here we firstly cloned three HIF‐α isoforms from the basal branches of Osteichthyes and used computational tools to characterise the molecular change underlying the functional divergence of HIF‐α isoforms in different lineages. Only the HIF‐1α and HIF‐2α in African lungfish and amphibians were found under positive selection. HIF‐1α and ‐2α were less functionally divergent in basal ray‐finned fish than in teleosts, and showed conserved but different transcriptional activity towards specific target genes. Abstract : All three HIF‐α isoforms are well preserved in basal ray‐finned fish. The HIF‐1α and ‐2α in amphibians and lungfish are positively selected. The HIF‐1α and ‐2α are more functionally diverged in teleosts. The HIF‐1α and ‐2α in different lineages exhibit different levels of activity.